Molecular correlates of glycine receptor activity in human β cells - Amanda Schukarucha Gomes; Cara E. Ellis; Aliya F. Spigelman; Theodore dos Santos; Jasmine Maghera; Kunimasa Suzuki; Patrick E. MacDonald (Molecular Metabolism)
Objectives: Glycine acts in an autocrine positive feedback loop in human β cells through its ionotropic receptors (GlyRs). In type 2 diabetes (T2D), islet GlyR activity is impaired by unknown mechanisms. We sought to investigate if the GlyR dysfunction in T2D is replicated by hyperglycemia per se, and to further characterize its action in β cells and islets. Methods: GlyR-mediated currents were measured using whole-cell patch-clamp in human β cells from donors with or without T2D, or after high glucose (15 mM) culture. We also correlated glycine-induced current amplitude with transcript expression levels through patch-seq. The expression of the GlyR α1, α3, and β subunit mRNA splice variants was compared between islets from donors with and without T2D, and after high glucose culture. Insulin secretion from human islets was measured in the presence or absence of the GlyR antagonist strychnine. Results: Although gene expression of GlyRs was decreased in T2D islets, and β cell GlyR-mediated currents were smaller, we found no evidence for a shift in GlyR subunit splicing. Glycine-induced currents are also reduced after 48 h culture of islets from donors without diabetes in high glucose, where we also find the reduction of the α1 subunit expression, but an increase in the α3 subunit. We discovered that glycine-evoked currents are highly heterogeneous amongst β cells, inversely correlate with donor HbA1c, and are significantly correlated to the expression of 92 different transcripts and gene regulatory networks (GRNs) that include CREB3(+), RREB1(+) and ZNF697(+). Finally, glucose-stimulated insulin secretion is decreased in the presence of the GlyR antagonist strychnine. Conclusions: We demonstrate that glucose can modulate GlyR expression, and that the current decrease in T2D is likely due to the receptor gene expression downregulation, and not a change in transcript splicing. Moreover, we define a previously unknown set of genes and regulons that are correlated to GlyR-mediated currents and could be involved in GlyR downregulation in T2D. Among those we validate the negative impact of EIF4EBP1 expression on GlyR activity.